Voting at 16? Youth suffrage is up for debate. Issue 2 (December 2013) - Zeglovits, Eva
In the debate on lowering the voting age, possible consequences have been discussed, among which are turn-out and the quality of the vote choice of newly enfranchised teenagers. Although findings on the turn-out of 16- and 17-year-olds are encouraging to supporters of youth suffrage, the results on political maturity are somewhat mixed. Most results stem from the case of Austria, where the voting age was lowered to 16 in 2007. They are supplemented with results of the Norwegian Voting Age Trial.